Presynaptic Versus Postsynaptic Localization of μ and δ Opioid Receptors in Dorsal and Ventral Striatopallidal Pathways - Olive, M. Foster (J Neurosci, 1997)
Parallel studies have demonstrated that enkephalin release from nerve terminals in the pallidum (globus pallidus and ventral pallidum) can be modulated by locally applied opioid drugs. To investigate further the mechanisms underlying these opioid effects, the present study examined the presynaptic and postsynaptic localization of δ (DOR1) and μ (MOR1) opioid receptors in the dorsal and ventral striatopallidal enkephalinergic system using fluorescence immunohistochemistry combined with anterograde and retrograde neuronal tracing techniques. DOR1 immunostaining patterns revealed primarily a postsynaptic localization of the receptor in pallidal cell bodies adjacent to enkephalin- or synaptophysin-positive fiber terminals. MOR1 immunostaining in the pallidum revealed both a presynaptic localization, as evidenced by punctate staining that co-localized with enkephalin and synaptophysin, and a postsynaptic localization, as evidenced by cytoplasmic staining of cells that were adjacent to enkephalin and synaptophysin immunoreactivities. Injections of the anterograde tracer Phaseolus vulgaris leucoagglutinin (PHA-L) or the retrograde tracer Texas Red-conjugated dextran amine (TRD) into the dorsal and ventral striatum resulted in labeling of striatopallidal fibers and pallidostriatal cell bodies, respectively. DOR1 immunostaining in the pallidum co-localized only with TRD and not PHA-L, whereas pallidal MOR1 immunostaining co-localized with PHA-L and not TRD. These results suggest that pallidal enkephalin release may be modulated by μ opioid receptors located presynaptically on striatopallidal enkephalinergic neurons and by δ opioid receptors located postsynaptically on pallidostriatal feedback neurons.